A comparative study on cylindrical and spherical models in fabrication of bone tissue engineering scaffolds: Finite element simulation and experiments. (1st December 2021) - Xu, Bowen; Lee, Kee-Won; Li, Wenjie; Yaszemski, Michael J.; Lu, Lichun; Yang, Yabin; Wang, Shanfeng
Graphical abstract: Highlights: Two circular-based models with cylindrical and spherical internal pore structures were designed. The porosity, surface area to volume ratio ( Sp / Vt ), compression/shear modulus, stress distribution, torsional rigidity, and hydraulic permeability of two types of unit cells were comprehensively explored. The precisely fabricated 3D printed scaffolds of poly(propylene fumarate) (PPF) supplied an excellent platform to systematically compare the simulative and experimental results. The present method can be extended to efficiently predict the mechanical properties and fluid permeability of other porous structures and their both in vitro and in vivo performance. Abstract: Tissue engineering scaffolds have been used for curing bone defects. Poly(propylene fumarate) (PPF) is promising in bone tissue engineering. The ideal scaffolds should have high porosity and sufficient mechanical properties. In this comparative study, two models with cylindrical and spherical pore structures have been designed in the Abaqus software based on the pore opening size ( L ) to strut length ( D ) ratio ( L / D ). Structural analyses including compression, shear, and torsion simulation were performed using finite element analysis (FEA). Compression experiments on the PPF scaffolds fabricated using projection micro-stereolithography (PμSL) were conducted with digital image correlation (DIC). Fluid simulation was further performed to investigate the fluid permeability of the scaffolds. The porosity and surface area ( Sp ) to volume ( Vt ) ratio ( Sp / Vt ) are found to be generally larger in the spherical pore unit cells than in the cylindrical ones. At the same L / D or porosity, the cylindrical pore unit cells have higher compression/shear modulus with better stress distribution, higher torsional rigidity, and higher hydraulic permeability than the spherical ones. This research provides guidance to the design of bone tissue engineering scaffolds as the bulk properties and fluid permeability of the scaffolds could be adjusted by using different pore structures with varied microstructure parameters.